Inteligencia artificial y spots políticos: la campaña presidencial de Guillermo Lasso en YouTube y en TikTok (2021) [Monográfico] - García Andrade, Esteban (2025)
This article merges the concepts of device, ideology and imaginary to analyze the impact of the machine learning algorithm, a type of AI, on the creation, production, circulation and consumption of Guillermo Lasso’s political spots, broadcast on YouTube and TikTok during the Ecuador 2021 Presidential Elections. On a qualitative level, the political spot operates as a technology of power and ideological matrix (significant dimension) that, enhanced by the machine learning algorithm (asignifying dimension), prepares the imaginary brain activity of the voter to imbue it with meaning through political narrative. At a quantitative level, the number of reproductions/viewings of certain political spots allows us to infer that the voter’s attention is transformed into a mechanism for the production of surplus value and the reproduction of power relations (attention economy). In summary, the structure of the article contains: i) the results of the democratic contest; ii) the results of the political communication campaign on YouTube and TikTok; iii) the function of the political spot as an ideological-imaginary device, explained from an audiovisual piece, considering the influence of the machine learning algorithm; iv) the discussion of Guillermo Lasso’s image on TikTok.